2021
DOI: 10.1001/jamaneurol.2021.0306
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Incidental Findings in Brain Magnetic Resonance Imaging in Children

Abstract: IMPORTANCE Incidental findings (IFs) are unexpected abnormalities discovered during imaging and can range from normal anatomic variants to findings requiring urgent medical intervention. In the case of brain magnetic resonance imaging (MRI), reliable data about the prevalence and significance of IFs in the general population are limited, making it difficult to anticipate, communicate, and manage these findings.OBJECTIVES To determine the overall prevalence of IFs in brain MRI in the nonclinical pediatric popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…This scoring convention was derived from an established rating scale ( 3 ). A similar 4-point rating scale has also been used with a population-based pediatric sample ( 5 ). In accordance with institutional neuroradiology practices, sinus findings were also reported when reviewing scans.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This scoring convention was derived from an established rating scale ( 3 ). A similar 4-point rating scale has also been used with a population-based pediatric sample ( 5 ). In accordance with institutional neuroradiology practices, sinus findings were also reported when reviewing scans.…”
Section: Methodsmentioning
confidence: 99%
“…The use of imaging in youth research with healthy and clinical populations gives rise to incidental findings that require a management strategy. The prevalence of incidental findings in imaging research, particularly neuroimaging, is well documented across the lifespan (1)(2)(3)(4)(5). Whereas studies have reported on incidental findings in clinically indicated imaging of youth (6,7), little is known regarding incidental findings among youth participating in imaging research in areas other than the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Another study estimated the overall rate at 34% ( Shoemaker et al, 2011 ), with the likelihood of IFs increasing with participant age ( Morris et al, 2009 ). A recent study, analyzing an Adolescent Brain Cognitive Development (ABCD) dataset of nearly 12,000 children ages 9 to 10 years, found an IF rate of 21% ( Li et al, 2021 ). Analyses of IFs in MRI research ( Illes 2006 ) have revealed that recommended policies range from having every scan read by a radiologist ( Milstein 2008 ), to having findings reviewed by an expert only if the researcher flags a brain abnormality ( Cramer et al, 2011 ), to having no scans read by a radiologist ( Royal and Peterson 2008 ).…”
Section: Core Elsi Issues In Designing and Conducting Field-based Mri Research In Remote And Resource-limited International Settingsmentioning
confidence: 99%
“…Disruption of neurulation and segmentation/cleavage impair neural tube closure and midline brain structures, expressed as major brain malformations such as neural tube defects and the holoprosencephaly spectrum in the susceptible fetus. These anomalies may be documented by prenatal sonography and fetal magnetic resonance neuroimaging [22], or only after birth with neonatal or childhood studies [23,24]. Sensitivity and specificity of the abnormal images obtained will be limited by the current technologies available for clinical applications.…”
Section: Early Pregnancy Effects On Embryonic/fetal Brainmentioning
confidence: 99%